The Relationship between Nutritional Knowledge, Attitudes, and Breakfast Habits among Junior High School Students in Tulungagung Regency - Adhitya Rizky Arissaputra Aswanto; Eka Sudibya; Prayitno Ribut Suwasono; Eunike Sri Puspaningsih (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2025)
Inadequate breakfast behavior among adolescents is a significant public health concern, contributing to decreased learning concentration and increased risk of malnutrition. Low nutritional knowledge is frequently identified as a contributing factor. This study aimed to analyze the relationship between the level of nutritional knowledge and breakfast attitude and behavior among adolescents in Tulungagung Regency. This was an analytical observational study utilizing a cross-sectional approach. The subjects consisted of 96 adolescent students selected from three Junior High Schools in the Tulungagung Regency area using a simple random sampling method. Data analysis was performed using the Pearson Product Moment and Spearman's Rank tests. The study results showed no significant relationship between the level of nutritional knowledge and breakfast attitude (p=0.991) or with breakfast behavior (p=0.084). These findings indicate that a high level of nutritional literacy does not necessarily guarantee the formation of a positive attitude and adherence to breakfast behavior among adolescents. Therefore, more applicable intervention strategies, such as implementing communal breakfast habits, are required to bridge the gap between knowledge and practice.